1995
DOI: 10.1164/ajrccm.152.5.7582317
|View full text |Cite
|
Sign up to set email alerts
|

Aging and hepatotoxicity of isoniazid and rifampin in pulmonary tuberculosis.

Abstract: We evaluated whether elderly patients with pulmonary tuberculosis and without apparent preexisting liver disease are at an increased risk to develop hepatotoxicity from an isoniazid-rifampin regimen and require regular liver function tests in comparison with younger patients. We analyzed the data of 131 patients treated in the period 1980-1985 of whom 64 (49%) were at least 60 yr of age. Subsequent increases of transaminases (measured weekly for as long as 4 wk after the start of treatment and later on when sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…However, the majority of studies show that the elderly are more susceptible to anti-TB drug induced hepatotoxicity (12, 13). Using a similar definition to that used in the present study (i.e., serum transaminase >3×the normal upper limit), Fernandez-Villar et al (30) found an 18.2% incidence of hepatotoxicity in the risk factor group (advanced age, chronic liver disease, abuse of alcohol, and others), and van den Brande et al (31) a 22% incidence of hepatotoxicity (transaminase increase >5 times the basal level) in elderly TB patients. Sharma et al (29) also reported a 16.2% drug-induced hepatotoxicity level in the elderly.…”
Section: Discussionmentioning
confidence: 71%
“…However, the majority of studies show that the elderly are more susceptible to anti-TB drug induced hepatotoxicity (12, 13). Using a similar definition to that used in the present study (i.e., serum transaminase >3×the normal upper limit), Fernandez-Villar et al (30) found an 18.2% incidence of hepatotoxicity in the risk factor group (advanced age, chronic liver disease, abuse of alcohol, and others), and van den Brande et al (31) a 22% incidence of hepatotoxicity (transaminase increase >5 times the basal level) in elderly TB patients. Sharma et al (29) also reported a 16.2% drug-induced hepatotoxicity level in the elderly.…”
Section: Discussionmentioning
confidence: 71%
“…In a recent Canadian series of 430 persons treated for active TB with isoniazid, rifampin, pyrazinamide, and ethambutol, 3% developed clinical hepatitis [16]. Other studies, using less defined measures, have reported rates of hepatocellular damage in у5% of patients receiving treatment for TB [17,18]. Therefore, the rates of hepatotoxicity found in the trials of LTBI in HIV-positive persons are in the range reported from most treatment studies, and the rates found in HIV-negative persons receiving rifampin plus pyrazinamide for treatment of LTBI are higher than expected.…”
Section: Discussionmentioning
confidence: 99%
“…For example, serum transaminases were used as an index of hepatotoxicity from combined isoniazid/rifampin therapy in pulmonary tuberculosis patients (Van Den Brande et al 1995). Before antituberculosis treatment, serum transaminase levels were similar in a group of 67 young patients (mean age, 38.6 years) and 64 elderly patients (mean age, 71.2 years); subjects with pre-existing hepatic disease were eliminated from the study.…”
Section: Liver and Kidney Disease In Elderly Individualsmentioning
confidence: 99%